Islamistic terror, the war on Iraq and the job prospects of Arab men in Britain: does a country's direct involvement matter? - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
This paper examines whether the labor market prospects of Arab men in England are influenced by recent Islamistic terrorist attacks and the war on Iraq. We use data from the British Labour Force Survey from Spring 2001 to Winter 2006 and treat the terrorist attacks on the USA on September 11th, 2001, the Madrid train bombings on March 11th, 2004 and the London bombings on July 7th, 2005, as well as the beginning of the war on Iraq on March 20th, 2003, as natural experiments possibly having led to a change in attitudes toward Arab or Muslim men. Using treatment group definitions based on ethnicity, country of birth, current nationality, and religion, evidence from regression-adjusted di_erence-in-di_erences-estimators indicates that the real wages, hours worked and employment probabilities of Arab men were unchanged by the attacks. This finding is in line with prior evidence from Europe.
Keywords: J71; J79; 330